2002
DOI: 10.1034/j.1600-0625.2002.110107.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of gene expression profiles in human keratinocyte mono‐layer cultures, reconstituted epidermis and normal human skin; transcriptional effects of retinoid treatments in reconstituted human epidermis

Abstract: In order to validate a model for predictive screening of dermatological drugs, we used a customized cDNA macro-array system containing 475 skin-related genes to analyze the gene expression patterns in human keratinocytes from different origins: (1) normal human epidermal keratinocyte mono-layer cultures, (2) the commercially available SkinEthic reconstituted human epidermis model, and (3) biopsies of normal human epidermis. Few markers of those that were detected significantly in keratinocyte mono-layers or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
1
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 63 publications
6
59
1
2
Order By: Relevance
“…Membranes were exposed for 4 days to a Molecular Dynamics Storm storage screen and scanned using a phosphorimager scanner (Molecular Dynamics Storm analyser; Amersham Biosciences). After local background substraction, an average signal intensity from duplicate spots was normalized for differences in probe labeling using the values obtained for housekeeping genes (24). For each gene, the IL-22-induced modulation was expressed as the relative expression value for stimulated vs control sample.…”
Section: Gene Expression Profiling Using Cdna Macroarraysmentioning
confidence: 99%
See 2 more Smart Citations
“…Membranes were exposed for 4 days to a Molecular Dynamics Storm storage screen and scanned using a phosphorimager scanner (Molecular Dynamics Storm analyser; Amersham Biosciences). After local background substraction, an average signal intensity from duplicate spots was normalized for differences in probe labeling using the values obtained for housekeeping genes (24). For each gene, the IL-22-induced modulation was expressed as the relative expression value for stimulated vs control sample.…”
Section: Gene Expression Profiling Using Cdna Macroarraysmentioning
confidence: 99%
“…Modification of the keratinocyte gene expression profile induced by IL-22 was analyzed using a cDNA array specially designed for the study of skin cells and keratinocytes and consisting of 475 different cDNAs, spotted in duplicate, that correspond to proteins involved in cell structure, metabolism, extracellular matrix, adhesion, differentiation, signaling, signal transduction, apoptosis, and stress (24). Analysis of Atlas cDNA array membranes revealed an IL-22-dependent increase in the expression of the calcium-binding protein S100A8 (GenBank accession no.…”
Section: Identification Of Il-22-induced Genes In Human Keratinocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effects of retinoids are often conflicting: retinoids can either stimulate or inhibit cell proliferation depending on the cell type affected or on the conditions used in cell cultivation (Amos and Lotan, 1990;Fisher and Voorhees, 1996;Rogers, 1997;Varani et al, 1989Varani et al, , 1991. Although the mechanism by which retinoids regulate the proliferation of epidermal cells is not completely understood, it has been shown that treatment of normal adult human skin and keratinocytes with tRA not only leads to thickening of the skin but also induces significant expression of several genes including HB-EGF (Bernard et al, 2002;Stoll and Elder, 1998;Varani et al, 2001). Induction of HB-EGF has also been reported in the skin of mice treated topically with tRA (Chapellier et al, 2002;Xiao et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Destes, podem ser citados fatores de crescimento epidérmico como o fator de crescimento derivado de plaquetas (PDGF -platelet derived growth factor) e o fator transformador de crescimento beta (TGF-β), que, por sua vez, influenciam a síntese de colágeno pelos fibroblastos 48 .…”
Section: Maria Fernanda Demattê Soares Belicounclassified